Fiber-reinforced composite with interpenetrating polymer network - Influence of shelf-life of the prepreg and the adhesive primer on interfacial adhesive strength of the composite to a resin luting material - Khan, Aftab (fi=Turun yliopisto|en=University of Turku|, 2021)
Fiber-reinforced composite (FRC) is a low-cost metal-free restorative alternative. To overcome problems related to the interfacial adhesion between composite luting material and FRC, a semi-interpenetrating polymer network (semi-IPN) matrix with linear polymer of poly(methylmethacrylate) (PMMA) was developed for FRC. Therefore, a series of laboratory studies were executed to investigate the effect of shelf-life, monomer systems and PMMA gradient on the intact and ground substrates of semi-IPN FRC. In the four experimental studies, everStick C&B was used as the semi-IPN based FRC. The first study evaluated the shelf-life and dissolving capability of the methyl methacrylate (MMA) monomer in polymerized FRC. The second study investigated the effect of different adhesive/primer on polymerized FRC which were stored for various durations (at 4°C; 1.0, 1.5, and 3-year) before curing. The third study analyzed the tensile bond strength (TBS) between resin luting material and FRC using different adhesive/primers systems. The fourth study determined TBS between polymerized FRC intact (high gradient PMMA) or ground (low gradient PMMA) surfaces and a resin luting material. The results were statistically analyzed using analysis of variance (ANOVA), the post hoc Tukey’s test, regression and correlation analysis using statistical software. It can be concluded that upon aging, the linear and cross-linked components of the semi-IPN structure of FRC might become phase-segregated. Both G-Multi PRIMER and Composite Primer might have the ability to diffuse into polymerized FRC and form a durable adhesive layer with increased nanohardness and adhesive strength between resin luting material and the FRC substrate. The highest TBS can be achieved for FRC intact surface treated with the G-Multi PRIMER.

Osittaislomittaismuoviverkostorakenne kuitulujitteissa muovissa – muovin esivalmisteen säilytysajan ja pinnan esikäsittelyajan vaikutus muovin rajapintaliitoksen sidoslujuuteen. Kuitulujittenen muovi on hammashoidon materiaali, joka täyttää hammaslääketieteen asettamat ulkonäölliset ja lujuusvaatimukset. Kuitulujitteinen muovi koostuu lujitekuiduista ja niitä sitovasta yleensä ristisilloitetusta muovimatriisista, joka voi olla myös osittaislomittaisverkostomuovirakenne (engl. semi-IPN). Tässä tutkimuksessa selvitettiin kuitulujite-esivalmisteen säilytysajan ja kovetetun kuitulujiteteisen muovin pinnan esikäsittelyn vaikutusta muovin liimautumiseen muihin hammaslääketieteessä käytettyihin muoveihin. Tutkimuksessa käytettiin semi-IPN muovipitoista kuitulujitteista muovia. Kuitulujitteisen muovin pinnan rakennetta ja ominaisuuksia tutkittiin muovin kovettamisen jälkeen. Vertailua tehtiin muun muassa nanomekaanisella pinnan analysoinnilla niistä muoveista, joiden esivalmistetta oli säilytetty jopa kaksi vuotta ennen näytteen valmistusta. Lisäksi tutkimuksessa kiinnitettiin erityistä huomiota kuitulujitteisen muovin liimautumiseen toiseen muoviin ja tällöin verrattiin erilaisten pinnan esikäsittelyaineiden vaikutusta rajapintaliitoksen sidoslujuuteen. Tulokset osoittivat tilastollisesti merkitseviä eroja näytteen pinnan nanokovuudessa pinnan eri kerrossyvyyksissä, mikä osoittaa semi-IPN gradienttirakenteen olemassaolon. Käytetyt kaksi esikäsittelyainetta saivat rajapintaliitoksen pinnan kovuuden lisääntymään näytteissä, jotka oli valmistettu tuoreesta kuitulujitteisen muovin esivalmisteesta. Myös esivalmisteen säilytysaika ennen sen käyttämistä vaikutti merkitsevästi liimautumiseen. Korkein sidoslujuus saavutettiin kuitulujitteisella muovilla, jonka pintaa ei oltu hiottu ennen liimaamista eli pinnan gradienttirakennetta ei oltu poistettu.